On the representation of non-linear functions by fractional-power series - Verlan, A.A.; Sterten, Jo (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2014)
A method for approximation of relationships by polynomials containing fractional-power terms is proposed, which in many cases makes it possible to cut down the number of computations. The proposed method for representation of relations by fractional-power polynomials features a smaller number of expansion terms while the approximation precision being the same as in the case of the «classical» methods. The method for finding the parameters of such expansions is considered; generalized spline of fractional order (smaller than or equal to unity) is defined. The experimental results on approximation of relations by fractional splines are presented.